1983
DOI: 10.1042/bj2140815
|View full text |Cite
|
Sign up to set email alerts
|

The fate of homologous 125I-labelled immunoglobulin G within rat visceral yolk sacs incubated in vitro

Abstract: When 125I-labelled rat IgG (immunoglobulin G) is incubated in vitro with visceral yolk sacs from 17.5-day-pregnant rats, the protein is readily degraded. The major radioactive digestion product that accumulates in the medium is [125I]iodo-L-tyrosine. When rotenone (10 microM) is also present in the incubation medium, the rate of digestion of IgG is inhibited to the same extent as the rate of pinocytosis of 125I-labelled polyvinylpyrrolidone. Proteolysis is likewise inhibited when either NH4Cl (30 mM) or leupep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…The endocytic index obtained for [14C]sucrose in the present study is similar to that reported for sucrose uptake in the rat yolk sac and other systems (Pratten et al, 1980). Weisbecker et al (1983) reported values of between 9.1 and 1 3.4u1/h per mg of protein for the endocytic index of 125I-labelled IgG incubated with rat yolk sac in the presence of calf serum, which are higher than the values obtained here for the guinea pig yolk sac. The difference may be attributable to the fact that a lower ligand concentration (1 jug/ml) was used in the rat yolk sac experiments.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The endocytic index obtained for [14C]sucrose in the present study is similar to that reported for sucrose uptake in the rat yolk sac and other systems (Pratten et al, 1980). Weisbecker et al (1983) reported values of between 9.1 and 1 3.4u1/h per mg of protein for the endocytic index of 125I-labelled IgG incubated with rat yolk sac in the presence of calf serum, which are higher than the values obtained here for the guinea pig yolk sac. The difference may be attributable to the fact that a lower ligand concentration (1 jug/ml) was used in the rat yolk sac experiments.…”
Section: Discussioncontrasting
confidence: 76%
“…However, pepstatin, a specific inhibitor of cathepsin D, had no detectable effect on IgG degradation. In order to give the tissue an opportunity to attain greater intracellular concentrations of the cathepsin inhibitors, experiments were carried out in which tissue was preincubated with leupeptin and pepstatin for 30min prior to addition of ligand, as described by Weisbecker et al (1983). Under these conditions the inhibition of degradation seen with leupeptin was slightly greater (47%) but, once again, no effect of pepstatin was found (results not shown).…”
Section: Degradation Of 25 I-labelled Iggmentioning
confidence: 99%
“…The value measured for copolymer 2 is typical of many substrates in this tissue [20]. Faster rates of exocytosis have been observed previously when using 121 I-labelled immunoglobulin G (IgG) [29] and 121 I-labelled formaldehyde denatured bovine serum albumin (dBSA) [29] as pinocytic substrates. The apparently faster release of dBSA was shown to be due to release of 125 I-labelled low molecular weight degradation products, not macromolecular dBSA.…”
Section: Discussionmentioning
confidence: 70%
“…The apparently faster release of dBSA was shown to be due to release of 125 I-labelled low molecular weight degradation products, not macromolecular dBSA. However, 115 I-labelled IgG was rapidly released from the yolk sac in both its intact form and as low molecular weight degradation products [29]. This IgG transport mechanism is an important physiological adaptation of the tissue to permit transport of passive immunity from mother to the developing embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our experiments using indium-111-labeled IgGs provide a more direct approach for identifying the sites of cumulative distribution and potential catabolism of IgG under physiological conditions. It is difficult to argue from the 125 I-labeled IgG data alone that any one tissue has a dominant role in the metabolism of IgG, since it is simultaneously proposed that 125 I-labeled degradation products are being rapidly exocytosed or diffused from this tissue 25 . As such, alternative residualizing labels for studying IgG distribution, which are more efficiently retained in tissues, should permit a more definitive assessment of the role of various tissues in IgG tissue catabolism 26 .…”
Section: Discussionmentioning
confidence: 99%